2011
DOI: 10.1002/mrc.2731
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and computational studies of nJ(77Se,1H) selenium–proton couplings in selenoglycosides

Abstract: Selenoglycosides are important starting materials in synthetic carbohydrate chemistry and play a role in biological interactions as well. Both aspects are influenced by the conformation around the glycosidic bond. Here, we present a combined experimental and computational approach to measure and evaluate (n)J((77)Se, (1)H) coupling constants for their use in conformational analysis. The measurements were carried out using a modified CPMG-HSQMBC pulse scheme which yields pure absorption antiphase multiplets to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…As an example, 2 J (Se,H 4a ) ≈ −1 Hz and 2 J (Se,H 4e ) ≈ +30 Hz in 1 , or 3 J (Se,H 4a ) ≈ 1 Hz, whereas 3 J (Se,H 4e ) ≈ 13 Hz in 6 . With our previous results as basis, we expected that these differences were to be accounted for the selenium lone pair effect for geminal couplings and the Karplus‐type relationship for vicinal coupling constants.…”
Section: Resultsmentioning
confidence: 95%
“…As an example, 2 J (Se,H 4a ) ≈ −1 Hz and 2 J (Se,H 4e ) ≈ +30 Hz in 1 , or 3 J (Se,H 4a ) ≈ 1 Hz, whereas 3 J (Se,H 4e ) ≈ 13 Hz in 6 . With our previous results as basis, we expected that these differences were to be accounted for the selenium lone pair effect for geminal couplings and the Karplus‐type relationship for vicinal coupling constants.…”
Section: Resultsmentioning
confidence: 95%
“…There seems to be a tendency for the J value to follow the dihedral angle. It has been reported that 2 J (Se, H) is strongly dependent on the orientation of the selenium lone pair and 3 J (Se, H) follows classical Karplus‐type equation from experimental and theoretical approaches . 2 J (Se, C) have not been studied intensively and little is known about 3 J (Se, C) values .…”
Section: Resultsmentioning
confidence: 99%
“…There are few applications of 77 Se‐NMR to carbohydrates . Perhaps most noteworthy has been a study by Harmark et al of the interaction between selenium‐labeled carbohydrates and lectins based on differences in 77 Se chemical shifts and line widths .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considered herewith are five most typical representatives of this series, compounds 1-5 (Scheme 1), obtained via heterogeneous Ni-based catalytic regioselective hydroselenation of terminal alkynes (to give compounds 1-3) and stereoselective hydroselenation of internal alkynes (to give compounds 4 and 5), as described elsewhere [3b] . Based on our previous results on the marked stereospecificity of geminal and vicinal J(Se,H) couplings in respect with the mutual orientation of the selenium lone pair and the corresponding coupling pathway in divinyl selenide, [4] selenophenes, [5] selenosugars [6] and selenium-containing heterocycles, [7] in this communication we employ vicinal selenium-proton couplings across double bond measured experimentally and calculated theoretically for the stereochemical study of 1-5 dealing with the internal rotation around the Se-C bonds. These results are supplemented with the energy-based theoretical conformational analysis performed at the MP2/6-311G * * level.…”
Section: Introductionmentioning
confidence: 99%